Pengaruh Proporsi Daging Ayam (Gallus gallus) dan Jantung Pisang (Musa paradisiaca) Terhadap Kadar Protein, Kadar Serat, Kadar Air dan Daya Terima pada Abon - Yuliana Salman; Ermina Syainah; Helmina Helmina; STIKES Husada Borneo; Politeknik Kesehatan Banjarbaru; Alumni STIKES Husada Borneo (Jurnal Kesehatan Indonesia, 2015)
Chicken and the heart banana is a resource with the possibility of producing a new food products that rich in proteins contained from chicken meat and crude fiber contained in the heart of the banana favorable economic value and high, because the consumption of plant fibers directly even less attractive company. This study aims to analyze the influence of the proportion of the chicken (Gallus gallus) and banana (Musa paradisiaca) on the content of protein, crude fiber, the water and acceptability of shredded. This study was experimental with randomized design. This study used four treatments and three times replication for analyze content of protein, fiber, and 2 times replication for the water content. Test methods for acceptability were hedonic organoleptic method (hedonic test). Method for analyze protein contents was Kjedahl, while crude fiber and the water content was the gravimetric method, statistical tests for acceptability using Friedman test. Data content of protein, crude fiber, and water content is one way ANOVA. Search results obtained any influence between the proportion of chicken and bananas in the protein shredded (p = 0.049) in the treatment p0 (43.05%) and p3 (30.45%), crude fiber content (p = 0.007) in the treatment p0 (6.66%), p3 and (13.72%) and water levels p = 0.000 for treatment p0 (5.82%) and p3 (30.85%). There is influence of color acceptability p = 0.001 in p0 treatment: 3,08 and 72% p3, there is no effect on the treatment p0 p1 p2 and p3 aroma (p = 0.188) , texture (p = 0.501), and taste (p = 0.138) shredded. Referring to the ISO standard on quality required of proteins are already qualified, while the crude fiber and the water do not meet the quality requirements.